2020
DOI: 10.1093/dote/doaa022
|View full text |Cite
|
Sign up to set email alerts
|

Long-term health-related quality of life after McKeown and Ivor Lewis esophagectomy for esophageal carcinoma

Abstract: Summary Introduction Both cervical (McKeown) and intrathoracic (Ivor Lewis) anastomosis of transthoracic esophagectomy are surgical procedures that can be performed for distal esophageal or gastro-esophageal junction (GEJ) cancer. The purpose of this study was to investigate the long-term health-related quality of life (HR-QoL) after McKeown and Ivor Lewis esophagectomy in a tertiary referral center. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…However, their main procedure was Ivor Lewis, which is different from our procedure of McKeown esophagectomy. McKeown esophagectomy has additional risks for laryngeal elevation disorder and recurrent nerve palsy compared to Ivor Lewis [13]. Sun et al reported early oral feeding on POD 1 for patients who underwent esophagectomy, including 3.2% of 3-field lymphadenectomy, was similar to late oral feeding on POD 7 with regard to postoperative pulmonary complications (22.1% vs. 28.6%, 95% confidence interval (CI): − 16.7-3.7%) and anastomotic leak (3.6% vs. 4.3%, 95% CI: − 5.3-3.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their main procedure was Ivor Lewis, which is different from our procedure of McKeown esophagectomy. McKeown esophagectomy has additional risks for laryngeal elevation disorder and recurrent nerve palsy compared to Ivor Lewis [13]. Sun et al reported early oral feeding on POD 1 for patients who underwent esophagectomy, including 3.2% of 3-field lymphadenectomy, was similar to late oral feeding on POD 7 with regard to postoperative pulmonary complications (22.1% vs. 28.6%, 95% confidence interval (CI): − 16.7-3.7%) and anastomotic leak (3.6% vs. 4.3%, 95% CI: − 5.3-3.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of the ERAS protocol after esophagectomy was successful with respect to complications, postoperative hospital stay, and costs [8,[11][12][13][14][15][16][17][18][19][20][21][22]25]. In addition, postoperative EN after thoracoscopic esophagectomy was more favorable than total parental nutrition for bodyweight loss (-2.94 ± 3.19% vs. 5.05 ± 3.65%, P = 0.020) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for esophageal cancer usually consists of surgery combined with perioperative chemical (radio) therapy [1]. The incidence of AL after McKeown esophagectomy remains relatively high, which may be related to tube gastric perfusion, anastomotic tension, construction of the anastomosis [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for esophageal cancer usually consists of surgery combined with perioperative chemical (radio) therapy [1]. The incidence of AL after McKeown esophagectomy remains relatively high, which may be related to tube gastric perfusion, anastomotic tension, construction of the anastomosis [1,2]. The Esophageal Complications Consensus (ECCG) classi ed AL into three types, typ I: local defect requiring no change in therapy or treated medically or with dietary modi cation; typ II: localized defect requiring interventional (not surgical) therapy, for example, drain placement or stenting; typ III: localized defect necessitates surgical therapy [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation